Effect of some situational variables on attitude of livestock owners towards artificial insemination in cattle - DANA, S S (The Indian Journal of Animal Sciences, 2013)
The availability of critical inputs was significantly and positively correlated with the attitude of livestock owners towards AI in cattle. Availability of a local breeding bull and conception rate of AI in cattie were significantly and negatively correlated. The liveslock owners having favourable attitude were characterized by not having a local breeding bull in their villages and these livestock owners fell high availability of critical inputs. Less number of inseminations required for a conception was one of the reasons for favourable altitude towards AI in cattle, whereae more number of inseminations required for a conception frustrate the livestock owners and they tend to develop unf avourable attitude towards AI in cattle.